NAVIGATING CHALLENGES AND OPPORTUNITIES: IMPLEMENTING HALAL PRINCIPLES IN THE SUPPLY CHAIN FOR SMALL AND MEDIUM ENTERPRISES IN THE FOOD SECTOR - Prita Ayu Kusumawardhany; Cepryana Sathalica Widyananda (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2024)
This research explores the challenges and opportunities associated with implementing halal principles in the supply chain for small and medium enterprises (SMEs) in the food sector. It examines the impact of awareness of halal raw materials, halal certification, and government support on business performance. The study finds that awareness of halal raw materials significantly enhances SMEs' competitiveness. Halal certification opens new market opportunities, and ensures compliance with safety standards, thereby improving overall business performance. Additionally, government support plays a crucial role in providing financial assistance, facilitating market access, promoting innovation, and simplifying regulatory compliance. Together, these factors contribute to the long-term sustainability and growth of SMEs in the halal industry. The research highlights the importance of integrating halal principles into business operations and offers recommendations for future studies to broaden the understanding of halal implementation across various industries.